Knowledge and Data Sharing - Annual Technical report 2023 - Ramírez, Margarita M.; Castiblanco, Claudia; Pizo, Cristian; Almanzar, Manuel R; Tanaka, Kenji; Tobon, Hector (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Throughout the past year, our commitment to advancing evidence-based decision-making has been fundamental in transforming the management of research integrity, quality, and value at the cluster level within the AICCRA project. We have cultivated a culture focused on results in project monitoring and evaluation (M&E), leveraging the capabilities of MARLO to streamline our planning and reporting processes. This strategic approach has significantly enhanced accountability and transparency, enabling informed strategic decision-making across the project. Overall, we upgraded our infrastructure to enhance security and stability, updated software for better performance, and provided extensive technical support. Tailored improvements included general enhancements, updates to the admin section, improvements to the homepage, contributions to performance indicators, and functionalities for deliverables. The Business Intelligence module and comprehensive online resources further emphasized our commitment to ensuring that all achievements in the project are publicly accessible and standardized among the country, regional and global teams.